DESAIN SISTEM PENDUKUNG KEPUTUSAN SELEKSI CALON KEPALA DESA DI KABUPATEN INDRAGIRI HILIR. - mafrizal mafrizal; ilyas ilyas (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2021)
Abstract A village is a legal community unit that has territorial boundaries that are authorized to regulate and administer government affairs, the interests of the local community based on community initiatives, rights of origin, and / or traditional rights that are recognized and respected in the government system of the Unitary State of the Republic of Indonesia. Village Government is the Village chief or what is referred to by any other name assisted by the Village apparatus as an element of Village Government administrators. To choose a candidate for village chief in accordance with the stipulated provisions that will be made as a candidate for village chief who will be elected, it must be adjusted to the feasibility of the village chief candidate's selection, so that the implementation of the village chief candidate selection can be aligned with the recipient's needs and avoid imbalances in selection and the selection process later. To assist in solving this problem, it is necessary to have a Decision Making System (SPK) so that any work related to decision making in the selection of prospective village chiefs can be helped in making a good decision according to the eligibility level of the participants to become candidate village chiefs. In the decision support system for selecting candidates for village chief, so that decision support is met, a decision support method for decision support systems is used, namely the Analytical Hierarchy Process (AHP) method. The results of the calculation showed that the main priority to become a participant in the Pilkades was Hendri as the first rank with a value of 0.395 or 39.5%. The indicators used in this comparison are: can recite the Koran, can give speeches, interview tests, and written tests. Abstrak Desa adalah kesatuan masyarakat hukum yang memiliki batas wilayah yang berwenang untuk mengatur dan mengurus urusan pemerintahan, kepentingan masyarakat setempat berdasarkan prakarsa masyarakat, hak asal usul, dan/atau hak tradisional yang diakui dan dihormati dalam sistem pemerintahan Negara Kesatuan Republik Indonesia. Pemerintah Desa adalah Kepala Desa atau yang disebut dengan nama lain dibantu perangkat Desa sebagai unsur penyelenggara Pemerintahan Desa. Untuk memilih calon kepala desa yang sesuai dengan ketentuan yang telah ditetapkan yang akan di jadikan sebagai calon kepala desa yang akan terpilih nantinya haruslah disesuaikan dengan kelayakan hasil seleksi calon kepala desa tersebut, agar pelaksanaan seleksi calon kepala desa dapat diselaraskan dengan kebutuhan penerima dan menghindari ketimpangan dalam seleksi serta proses pemilihan nantinya. Untuk membantu dalam memecahkan masalah tersebut perlu adanya suatu Sistem Pengambilan Keputusan (SPK) agar setiap pekerjaan yang menyangkut pengambilan keputusan dalam seleksi calon kepala desa dapat terbantu dalam mengambil suatu keputusan yang baik yang sesuai dengan tingkat kelayakan peserta untuk dijadikan calon kepala desa. Pada sistem pendukung keputusan seleksi calon kepala desa ini agar pendukung keputusannya terpenuhi maka digunakan sebuah metode penunjang keputusan untuk sistem pendukung keputusan yaitu metode Analytical Hierarchy Process (AHP). Hasil perhitungan yang didapat bahwa yang menjadi prioritas utama untuk dijadikan sebagai peserta pada pilkades yaitu Hendri sebagai peringkat pertama dengan nilai 0.395 atau 39,5%. Indikator yang digunakan dalam perbandingan ini yaitu: bisa mengaji, bisa berpidato, tes wawancara, dan tes tertulis.